THE EFFECT OF TEACHER COMPETENCE ON STUDENT LEARNING OUTCOMES: A SURVEY STUDY AT SMA BINA PANGUDI LUHUR - Syakur, Asadur Rahman; Nahuda, Nahuda; Ulfa, Maria (Tahdzib Al-Akhlaq: Jurnal Pendidikan Islam, 2025)
This study aims to determine the effect of teacher competence on student learning outcomes at Bina Pangudi Luhur Senior High School. The teacher competence studied covers four main aspects: pedagogical, professional, personality, and social competence. The approach used was quantitative with a survey method. Data were collected through questionnaires distributed to grade 10 students as respondents. Learning outcomes were measured based on report card scores from the odd semester of the 2024/2025 academic year. Data analysis was conducted using simple linear regression to test the extent of teacher competence's influence on student learning outcomes. The results showed a positive and significant effect between teacher competence and learning outcomes. The higher the level of teacher competence, the better the achievement of student learning outcomes. This finding emphasizes the importance of improving teacher competence as a strategy in efforts to improve the quality of education at the high school level.